Harnessing the power of equine assisted counseling : adding animal assisted therapy to your practice - Trotter, Kay Sudekum (New York : Brunner-Routledge, 2012)
"This book will help licensed professional counselors incorporate Equine Assisted Counseling (EAC) into their practices, even those who have no prior experience working with horses. It provides a strong research foundation for understanding the efficacy of equine assisted interventions and the potentially powerful impact that a horse can have in creating a new counseling dynamic. Chapters address using horses to help clients dealing with various traumas and abuse, anxiety, depression, atypical behaviors, and social skills and communication issues. One chapter is written by the internationally renowned "horse whisperer" Pat Parilli and offers a look at EAC from the horse's point of view and describes the process of developing a relationship with the horse in a positive, safe, and respectful manner, an important topic to ensure the well-being of the horse throughout a session. Counselors will find this a valuable resource for understanding and utilizing EAC as a new resource in their own practices, as will students seeking to learn about this innovative approach"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Horses -- Therapeutic use; Horsemanship -- Therapeutic use; Psychotherapy; Horses -- Psychological aspects; Human-animal relationships; Electronic books